KUNJUNGAN IBU BALITA KE POSYANDU. APAKAH FAKTOR REINFORCING BERPENGARUH? - Muhamad Nor Mudhofar; Emmy Putri Wahyuni; Fibrinika Tuta Setiani; Susanti Pratamaningtyas (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Posyandu, or Integrated Health Service Posts, are a form of Community-Based Health Initiatives (CBHI) organized by, for, and with the community to facilitate access to basic health services at the community level. The objective of this study was to determine the relationship between reinforcing factors and visits by mothers of toddlers to Posyandu. A cross-sectional study design was used in this research. The study was conducted in Salumaka Village. The research was carried out in September 2025. The study population consisted of all mothers with toddlers in Salumaka Village. The study sample comprised 85 respondents. The sampling technique used was purposive sampling. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results of the study indicate a significant association between the role of health cadres (p-value: 0.000) and spousal support (p-value: 0.002) and mothers’ visits to the Posyandu. It is recommended that village midwives and health cadres consistently provide information on the importance of the Posyandu and encourage the involvement of the family, particularly the husband, so that mothers regularly visit the Posyandu to maintain their own health and monitor the growth and development of their infants and toddlers. Keywords: Support from the Husband, the Mother of a Toddler, and the Posyandu.